Аксиома ольвийской просопографии IV – I вв. до н. э. - Николаев, Н.И. (Історичний архів. Наукові студії, 2014)
Путем системных исследований установлено, что эпонимный каталог Ольвии
IosPE I2
201 – календарь этого полиса, содержит основные генеалогические,
хронологические (абсолютные и относительные даты) и просопографические
сведения о главных элитных родах Ольвии IV – I вв. до н.э. Просопографические
исследования догетской Ольвии невозможны без опоры на этот документ. Шляхом системних досліджень встановлено, що епониімний каталог Ольвії IosPE I2
201 – календар цього полісу, містить основні генеалогіні, хронологичні (абсолютні та
відносні дати) й просопографічні відомості про головні елітні клани Ольвії IV – I ст.
до н.е. Просопографічні дослідження догетськоі Ольвії неможливі без опори на цей
документ. Traditionally, for a long historical period, all institutions of state and religious authorities
(magistrates, priests, eponymous) in Olbia were represented by a small group of people from
elite families. Available for studying facts of Olbian social and political history are associated in
a varying degree with this category of population. It determines the relevance of research for
systematizing the information about Olbian elite and therefore the formation of the ground of
Olbian prosopography. Herewith, historical events acquire the names of their participants-real
individuals. Prosopographic information is concentrated in the most diverse (including
fragmented) sources (narrative sources, lapidary inscriptions, graffiti, stamps, coins, etc.)
detected during the entire period of study of Olbia. The contemporary stage of research is
characterized by an attempt to synthesize these disparate data. This became possible with the
introduction for scientific revolution of the eponymous catalogue ІosPE I2 201 – the calendar of
Olbia. For this document is extremely complex and multi-layered, its effective study is possible
only on the basis of system analysis methods. The purpose of this article is to overview the
main areas of prosopographic research of Olbian eponymous catalogue: the history of study of
Olbian prosopography, internal (prosopographic) communications of the catalogue, the
communication of various families in the catalogue, chronological periods of ups and downs of
the families in the catalogue. This is followed by the overview of external relations: the
catalogue and narrative sources, prosopographic study out of chronological borders of the
catalogue and in the gaps of the catalogue, the catalogue and lapidary inscriptions of Olbia, the
catalogue and inscriptions of other cities, catalogue and coin legends, monograms and
reduction, catalogue and inscriptions on the ceramic stamps and weights, catalogue and graffiti,
catalogue and the inscription on the lead plates. Prospects and problems of forming the
foundations of Olbia prosopography IV – I centuries BC are also concidered. The main principle
of Olbian prosopography is formulated in the final part: eponymous catalogue IosPE I2
201
contains the basic genealogical, chronological (absolute and relative dates) and prosopographic
information about main elite families of Olbia IV – I centuries BC. Prosopographic research of
pre-Geths Olbia is impossible without reference on this document. Example: in the article of V.F.
Stolba (A Prosopographical Note on IOlbia 71 (Dubois IGDOlbia 11)//Miscellanea. –
Mnemosyne.– 2012.) the basic principle of Olbian prosopography is ignored . As the result the
historical facts of Olbia of the IV – III-d centuries BC are distorted. The another example: the
decree in honor of Nikeratus (IosPE I2 34) dates from the first two decades of the II-d century
BC. However, I haven’t found the prosopographic information confirming such a dating in
eponymous catalogue. This was the basis for reconsidering the date of the decree in honor of
Nikeratus IosPE I2 34 and for attributing it to the I AD.